Association of acanthosis nigricans and skin tags with insulin resistance Associação de acantose nigricante e acrocórdons à resistência insulínica - Mariana Tremel Barbato; Paulo Ricardo Criado; Ana Kris da Silva; Evelyne Averbeck; Marina Bensen Guerine; Naiana Bittencourt de Sá (Sociedade Brasileira de Dermatologia, 2012)
Insulin resistance is a metabolic disorder in which target cells fail to respond to normal levels of circulating insulin. Insulin resistance has been associated with presence of acanthosis nigricans and acrochordons. It is known that early diagnosis and early initial treatment are of paramount importance to prevent a series of future complications. These dermatoses may represent an easily identifiable sign of insulin resistance and non-insulin-dependent diabetes. A resistência insulínica é uma alteração metabólica caracterizada por falhas das células-alvo em responder aos níveis normais de insulina circulante. A resistência insulínica já foi relacionada à presença de acantose nigricante e de acrocórdons. Sabe-se que o diagnóstico e o início do tratamento precoce são de suma importância para prevenção de uma série de manifestações futuras. Estas dermatoses podem representar um sinal facilmente identificável para rastreamento de resistência à insulina e do diabetes mellitus não insulinodependente.